Solubility product of a Nb–N bearing austenitic stainless-steel biomaterial - Kayron Lima Silva; Samuel Filgueiras Rodrigues; Glaucia Maria Evangelista Macedo; Bruno Leonardy Sousa Lopes; Clodualdo Aranas, Jr.; Fulvio Siciliano; Gedeon Silva Reis; Eden Santos Silva (Journal of Materials Research and Technology, 2021)
This research investigates the Z-Phase solubility product of austenitic stainless steel (ASS) ASTM F-1586 used as orthopedic implants under the solubilization procedure. Precipitate extraction by an electrolytic separation technique and analytical thermodynamic calculations as a function of the solubilization temperature and chemical composition were employed. In the first procedure of preferential electrolytic phase dissolution, samples were submitted to a solubilization treatment, followed by quenching. The specimens were subjected to a surface treatment then dissolved in solution. Following the dissolution, the electrolyte was vacuum filtered on a 0.20 μm polyvinylidene difluoride (PVDF) membrane and vacuum dried for 24 h. The microstructures were characterized via scanning electron microscopy (SEM/EDS) and transmission electron microscopy (TEM/EDX) techniques. The results revealed by the Z-phase (Cr2Nb2N2) precipitation potential (Ks) that the precipitates acted as a softening inhibitor agent and retarded the grain growth at lower solubilization temperature conditions (Ts < 1100 °C). The considerable amount of fine precipitates were mainly formed due to the nucleation and coalescence of Cr/NbN in the matrix. On the other hand, larger precipitates nucleated and coalesced above 1200 °C, and had their volume fraction reduced at this condition.